Insight into the development of versatile dentin bonding agents to increase the durability of the bonding interface - Porto, Isabel Cristina Celerino de Moraes; Lôbo, Teresa de Lisieux Guedes Ferreira; Rodrigues, Raphaela Farias; Lins, Rodrigo Barros Esteves; da Silva, Marcos Aurélio Bomfim (Frontiers in Dental Medicine, 2023)
Despite the huge improvements made in adhesive technology over the past 50 years, there are still some unresolved issues regarding the durability of the adhesive interface. A complete sealing of the interface between the resin and the dentin substrate remains difficult to achieve, and it is doubtful whether an optimal interdiffusion of the adhesive system within the demineralized collagen framework can be produced in a complete and homogeneous way. In fact, it is suggested that hydrolytic degradation, combined with the action of dentin matrix enzymes, destabilizes the tooth-adhesive bond and disrupts the unprotected collagen fibrils. While a sufficient resin–dentin adhesion is usually achieved immediately, bonding efficiency declines over time. Thus, here, a review will be carried out through a bibliographic survey of scientific articles published in the last few years to present strategies that have been proposed to improve and/or develop new adhesive systems that can help prevent degradation at the adhesive interface. It will specially focus on new clinical techniques or new materials with characteristics that contribute to increasing the durability of adhesive restorations and avoiding the recurrent replacement restorative cycle and the consequent increase in damage to the tooth.